SEMANGAT KEBANGSAAN DALAM KITAB AL-NAGHAM KARYA KH. AHYAUDDIN IBN KH. ANWAR IBN HAJI KUMPUL SERIBANDUNG, SUMATERA SELATAN - Zulkarnain Yani (Balai Penelitian dan Pengembangan Agama Jakarta, 2018)
This paper presents the results of research of one of the work of South Sumatra scholars in Seribandung Village. The scholars was named KH. Ahyauddin Ibn KH. Anwar Ibn Haji Kumpul Seribandung with his book entitled al-Nagham. The Book of al-Nagham is composed using Arabic and Malay Arabic script in the form of a printed book. What's interesting about this book to be studied is because the contents of the book content to inflame the national spirit through song lyrics are arranged directly by KH. Ahyauddin. Through this book, KH. Ahyauddin inflame the spirit of nationalism to his santrinya. The spirit of nationality conveyed by him in this book, among others, love the homeland, patriotism and unity. This book taught in Pondok Pesantren since mid-1963 until 2009 Tulisan ini menyajikan hasil penelitian salah satu karya ulama Sumatera Selatan yang ada di Desa Seribandung. Ulama tersebut bernama KH. Ahyauddin Ibn KH. Anwar Ibn Haji Kumpul Seribandung dengan kitabnya berjudul al-Nagham. Kitab al-Nagham ini disusun menggunakan aksara Arab berbahasa Arab dan Melayu dalam bentuk kitab cetakan. Yang menarik dari kitab ini untuk dikaji adalah karena kandungan isi kitab tersebut menggelorakan semangat kebangsaan melalui syair-syair lagu yang disusun langsung oleh KH. Ahyauddin. Melalui kitab ini, KH. Ahyauddin mengobarkan semangat kebangsaan kepada para santrinya. Semangat kebangsaan yang disampaikan olehnya dalam kitab ini antara lain cinta tanah air (hubb al-wathan), patriotisme, persatuan dan kesatuan. Kitab ini diajarkan di pondok pesantren sejak pertengahan tahun 1963 hingga tahun 2009.